The Strong Consistency of the Estimator of Fixed-Design Regression Model under Negatively Dependent Sequences. (26th November 2013) - Wang, Xuejun; Ge, Meimei; Hu, Shuhe; Wang, Xize
Abstract : We study the strong consistency of estimator of fixed design regression model under negatively dependent sequences by using the classical Rosenthal-type inequality and the truncated method. As an application, the strong consistency for the nearest neighbor estimator is obtained.